A09 Stage- and cell-specific changes of nucleolar activity and integrity are associated with the progression of huntington's disease. (September 2018) - Sönmez, Aynur; Kojer, Kerstin; Mustafa, Rasem; Spieth, Salome; Litke, Christian; Koch, Jenniver; Hering, Tanja; Liss, Birgit; Orth, Michael; Parlato, Rosanna
Abstract : Background: Transcriptional and metabolic dysregulation are known to occur in Huntington's disease (HD). Mutant huntingtin (mHTT) protein affects several cellular functions hindering the identification of the primary pathogenic event. Impaired transcription of ribosomal DNA (rDNA) genes in the nucleolus – a major non-membrane bound sub-nuclear compartment – represents an emerging mechanism underlying progressive neurodegeneration Aims: To identify a sensitive transcriptional and metabolic marker associated with mHTT and disease progression, we tested the hypothesis that changes in rDNA transcription in the nucleolus are early signs of transcriptional dysregulation by mHTT in HD models and human tissue biopsies. Methods/techniques: We analyzed by real-time quantitative PCR, RNA in situ hybridization, and immunofluorescence the activity and integrity of the nucleolus in the striatum and skeletal muscle of zQ175 knock-in mice at various ages as well as of patient tissue biopsies at early neuropathological stages. Results/outcome: Here, we show that rDNA transcription and distribution of the nucleolar chaperone protein nucleophosmin (NPM1) are differentially altered in brain and muscle tissues from HD mouse models and in muscle biopsies from HD patients. Conclusions: Our results indicate that mHTT nuclear inclusions interfere with nucleolar function in a stage- and cell-specific fashion by altering NPM1 in striatal cells. Moreover these studies demonstrate that NPM1 in muscle cells constitutes a molecular signature of the initial stages of HD. These findings could help to provide novel tools to test the functional efficacy of ongoing therapeutic strategies aiming at lowering mHTT levels in specific cells. Funding: This work was supported by EHDN seed-fund project 0753, DFG PA 1529/2–1, CEMMA Graduate School